2021
DOI: 10.1542/peds.2021-052673
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory Diagnoses Following Hospitalization for a Brief Resolved Unexplained Event

Abstract: BACKGROUND AND OBJECTIVES: Most young infants presenting to the emergency department (ED) with a brief resolved unexplained event (BRUE) are hospitalized. We sought to determine the rate of explanatory diagnosis after hospitalization for a BRUE.METHODS: This was a multicenter retrospective cohort study of infants hospitalized with a BRUE after an ED visit between October 1, 2015, and September 30, 2018. We included infants without an explanatory diagnosis at admission. We determined the proportion of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…There are only 9 studies in the literature that investigate BRUE/ALTE and ED usage. [10][11][12][13][14][15][16][17][18] Usage focused on clinical characteristics in a handful of studies. 12,13,16,18 None of these studies examined the role of potential social determinants.…”
Section: Discussionmentioning
confidence: 99%
“…There are only 9 studies in the literature that investigate BRUE/ALTE and ED usage. [10][11][12][13][14][15][16][17][18] Usage focused on clinical characteristics in a handful of studies. 12,13,16,18 None of these studies examined the role of potential social determinants.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, the Italian Society of Pediatrics updated its own guidelines and accepted the new acronym BRUE for lower-risk idiopathic episodes, while keeping the term ALTE for severe idiopathic episodes that are only solved after resuscitation maneuvers and related to patient instability, prematurity (<32 weeks of gestational age and <43 weeks of postconceptional age), age below two months, need for resuscitation maneuvers, recurrence, and poor family compliance [51,53]. Clinical evaluation of children with BRUE showed that, in the great majority, children with this diagnosis have very mild disease that does not require hospital admission for further tests [59,60].…”
Section: Apparent Life-threating Event (Alte) and Brief Resolved Unex...mentioning
confidence: 99%
“…Following the publication of the AAP guidelines, studies showed that while the majority of infants presenting with a BRUE (87%–92%) met at least one higher-risk criteria, only a small proportion have a serious underlying diagnosis (4%) 2 6–8. Analysis of the AAP criteria identified a history of a similar event, event clusters, CPR use and abnormal medical history to be associated with a serious underlying diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, 15 children’s hospitals across the USA convened to create BRUE Quality Improvement and Research Collaborative (BRUE-QIRC) network 6–8 10 11. Using an administrative database (Pediatric Health Information System), the collaboration was able to retrospectively identify the largest cohort of patients with BRUE described to date (n=3283).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation